USING STATISTICAL APPROACHES IN STUDYING THE IN COMMON EFFECT OF SOME CHEMICAL AND PHYSICAL CHARACTERISTICS ON PEDOGENIC DISTRIBUTION OF MANGANESE FOR SOME SOILS IN NINEVEH PROVINCE - Saleh Mawlood; Mohammed Tahir Said Khalil (Mesopotamia Journal of Agriculture)
Forty soil samples were collected from eight soil profiles representing Fadhlia, Kara-Tapa, and Hamdania locations in Nineveh province / northern of Iraq.Soil manganese were extracted by DTPA, GAc and DCB. Statistical approaches were applied to predict levels of extractable manganese values. Results indicated that in common effect of some chemical and physical properties with dissolution methods on pedogenic distribution of manganese were existed. By using stepwise multiple linear regression models , highly qualified in common effect was noticed between pedogenic distribution of manganese extracted by DTPA with. organic matter, clay content and soil pH with total effect of 75.5% and a positive correlation (r = 0.869). However effect of EC , Ca+2, Na+ and Cl- was found on manganese extracted by glacial acetic acid with total effect of 27% and positive correlation (r = 0.520). Lower effect was found between pH , Mg+2 and K+ ions and DCB extractable manganese with total effect of 26% and correlation coefficient (r = 0.114). Mathematical models were contrived to predict manganese levels extracted by different methods due to characteristics effects for each.